SPEECH STYLE USED IN THE NOVEL “NEMESIS” BY AGATHA CHRISTIE - Alifiah, Ananda Nur; Abdullah, Abdullah (Journal of English Literature and Linguistic Studies, 2023)
Speech style can be interpreted as the variation of language that is influenced by the level of formality. The level of formality is determined by several aspects, such as the topics of the conversation and the social status of the speakers. Martin Joos (1967) classifies speech style into 5 types, including Frozen style, Formal style, Consultative style, Casual style and Intimate style. Furthermore, it is known that everyone uses different speech styles depending on the reason they use it. In order to comprehend the speech style, the researcher chooses one of the works by a novelist named Agatha Christie entitled Nemesis. The purposes of this research are to find out the speech styles used by the main character of the novel “Nemesis” by Agatha Christie and to explore the reason for the speech styles used by the main character of the novel “Nemesis” by Agatha Christie. To conduct this research, the researcher used a qualitative descriptive method. There are 2 theories which are used in this research, the first theory is Speech style theory from Martin Joos and the second theory is Holmes’ theory of aspects that affect language variation. There are 2 outcomes of this research. The first, the main character of the novel “Nemesis” by Agatha Christie – Miss Marple – uses 4 types of speech styles out of 5 types, including Formal style with 18 data, Consultative style with 143 data, Casual style with 92 data, and Intimate style with 8 data. The second, the main reasons why Miss Marple uses those speech styles is the participants followed by the factors of the setting, the topic as well as the function.